Data Mining and Polar Coordinates in the Analysis by Gender of Finishing Behaviors in Professional Basketball Pick and Roll - Morillo-Baro, Juan Pablo; Troyano-Gallegos, Belén; Pastrana-Brincones, José Luis; Vázquez-Diz, Juan Antonio; Reigal, Rafael E.; Quiñones-Rodríguez, Yarisel; Hernández-Mendo, Antonio; Falcó, Coral; Morales-Sánchez, Verónica (Frontiers in Sports and Active Living, 2021)
Basketball open nature gives it a large uncertainty that makes hard the tactical analysis of the situations happened in the game. Specifically, blocks are one of the offensive tactical elements most used in basketball, and one example of a tactical situation that need the highest preparation level to get a good performance in the competition. The aim of this study is to differentiate these player behaviors by gender using Data Mining and Polar Coordinates analysis. Therefore, one ad hoc observational tool made by 17 criteria and 97 exhaustive and mutually exclusive (E/ME) categories has been designed and validated using the Data Quality analysis (correlation coefficients and concordance index ˃0.98) and Generalizability analysis (G coefficients ˃0.94) in order to do such study. The observational design is nomothetic, punctual and multidimensional. 176 direct blocking situations has been analyzed for the men's category and 118 for women's category, corresponding to three different teams of each gender playing in the highest competition level in Spain in the 2018/2019 season using Hoisan software tool. The analysis of the relationships among behaviors has been performed using Polar Coordinates analysis as well as Data Mining analysis: clustering and decision tree classifier. Results show significant relationships that allow us to tactically interpret the Pick and Roll situations in men's and women's professional basketball players in Spain, allowing us to develop more intervention programs which will optimize training and improve players performance.